Optimalisasi Model ARIMA dalam Prakiraan Curah Hujan di Jambi - Nandarie, Alya Claudina Anggun; Al Badri, Abdul Aziz; Haryanto, Yosafat Donni (GEOGRAPHIA : Jurnal Pendidikan dan Penelitian Geografi, 2023)
Process determine predicted monthly rainfall values for 2022, this study models rainfall forecasts. Observations of monthly rainfall over 30 years (1992–2022) were used to collect the data. The data is then analyzed using the Minitab application’s ARIMA model to examine historical trends. For each model utilized, the forecast results are connected with the actual observation data in 2022. The model (1,0,1), (1,0,1) is used to calculate the difference to acquire a result of 54%, which is the best correlation value. The most accurate model for predicting monthly rainfall in Jambi is this one.